2018
DOI: 10.1111/febs.14626
|View full text |Cite
|
Sign up to set email alerts
|

Efficient SSA‐mediated precise genome editing using CRISPR/Cas9

Abstract: CRISPR/Cas9 has been emerging as a main player in genome editing field since its advent. However, CRISPR/Cas9-induced precise gene editing remains challenging since it requires no scar left after editing. Among the few reports regarding two-step 'pop in & out' technologies for precise gene editing, the combination of CRISPR/Cas9 with Cre/LoxP demonstrates a higher efficiency, but leaves behind a 34-base pair of tag sequence due to its inherent property. Another method utilizes piggyBac transposon for removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Other forms of modifications, such as large deletions and inversions, can also be achieved using optimized endonucleases. In addition to NHEJ and HDR, a single-strand annealing (SSA) repair mechanism can also be utilized to mediate modifications by inducing the deletion of an intervening fragment between two homogenous repeat sequences (Li et al, 2018c).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…Other forms of modifications, such as large deletions and inversions, can also be achieved using optimized endonucleases. In addition to NHEJ and HDR, a single-strand annealing (SSA) repair mechanism can also be utilized to mediate modifications by inducing the deletion of an intervening fragment between two homogenous repeat sequences (Li et al, 2018c).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…This is subsequently followed by a second step that results in the excision of a marker from the knockin cassette during precision editing of the target locus, allowing enrichment by negative selection. 32,33 Importantly, a recent report demonstrated that HDR-dependent insertion of a selectable marker at one locus coincides with one or more independent HDR-mediated edits at other loci. The concept forms the basis for a strategy has been termed "co-targeting with selection," which can be used to efficiently enrich for HDR-proficient cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, the removal of the selection is often required to allay concerns of marker-dependent effects. There are several "pop in and out" two-step techniques for markerfree genome engineering, including the Cre/LoxP system (Zhu et al, 2015), the piggyBac transposon (Xie et al, 2014), and the SSA repair mechanism (Li et al, 2018). This Research Topic presents a protocol article for biallelic HDR targeting using piggyBac-mediated selection removal (Jarazo et al).…”
Section: Editorial On the Research Topic Precise Genome Editing Technmentioning
confidence: 99%